2018
DOI: 10.1016/j.jss.2017.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the relationship between flow-mediated vasodilation and radial artery tonometry in peripheral artery disease

Abstract: In an analysis of vascular surgery outpatients, no correlation between FMD and AIX was detected. Larger prospective studies are needed to determine whether the inclusion of both parameters improves predictive models for the early identification and potential risk stratification of PAD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…In addition to the macrovascular blood flow restriction, work from our group and others suggests that patients with PAD exhibit "microvascular disease" seen as a thickening of capillary basement membranes, perivascular fibrosis, and impaired endothelial reactivity. [16][17][18][19] This microvascular disease further impairs the delivery of oxygen and nutrients to the affected tissues. Moreover, studies of permeabilized myofibers have demonstrated a significant dysfunction in the mitochondria of affected muscle cells, decreasing the ability of the muscle to effectively use the delivered oxygen and nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the macrovascular blood flow restriction, work from our group and others suggests that patients with PAD exhibit "microvascular disease" seen as a thickening of capillary basement membranes, perivascular fibrosis, and impaired endothelial reactivity. [16][17][18][19] This microvascular disease further impairs the delivery of oxygen and nutrients to the affected tissues. Moreover, studies of permeabilized myofibers have demonstrated a significant dysfunction in the mitochondria of affected muscle cells, decreasing the ability of the muscle to effectively use the delivered oxygen and nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…18 For patients with PAD, arterial stiffness has mainly been analyzed in claudicants, also with the objective of assisting cardiovascular risk analysis. 10 - 13 There are few studies evaluating patients with an advanced stage of PAD. 14…”
Section: Discussionmentioning
confidence: 99%
“…9 Almost all of these studies were performed in patients with early stage, asymptomatic PAD or claudication. 10 - 13 There is no consensus on whether patients with advanced PAD have increased arterial stiffness. Brand et al demonstrated that patients with CLI had high central aortic pulse pressures and AIx values, but a much reduced PWV.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial function was measured by brachial artery FMD using previously described methods. 21 A blood pressure cuff was placed on the upper arm, and B-mode ultrasound (Philips HD11; Philips Healthcare, Andover, Mass) with a broadband linear array transducer with a 3-12 MHz range (Philips L12-3) was used to locate the brachial artery. The mean diameter at baseline was then measured.…”
Section: Measurementsmentioning
confidence: 99%